The impact of gamification on students’ learning, engagement and behavior based on their personality traits - Smiderle, Rodrigo; Rigo, Sandro José; Marques, Leonardo B.; Peçanha de Miranda Coelho, Jorge Arthur; Jaques, Patricia A. (Smart learning environments, 2020)
The gamification of education can enhance levels of students’ engagement similar to what games can do, to improve their particular skills and optimize their learning. On the other hand, scientific studies have shown adverse outcomes based on the user’s preferences. The link among the user’s characteristics, executed actions, and the game elements is still an open question. Aiming to find some insights for this issue, we have investigated the effects of gamification on students’ learning, behavior, and engagement based on their personality traits in a web-based programming learning environment. We have conducted an experiment for four months with 40 undergraduate students of first-year courses on programming. Students were randomly assigned to one of the two versions of the programming learning environment: a gamified version composed of ranking, points, and badges and the original non-gamified version. We have found evidence that gamification affected users in distinct ways based on their personality traits. Our results indicate that the effect of gamification depends on the specific characteristics of users. First part title: Studying the impact of gamification on learning and engagement based on the personality traits of students